(untitled) (Mantichora. Italian Journal of Performance Studies, 2020)
The object of the paper is the latest theatrical production of one of the most influent director of XX century: Yuri Lyubimov. His provocative and innovative style is well known thanks to his performances staged in USSR and abroad, but we would to consider his productions of the last ten years. The aim of such circumscribed analysis is to demonstrate how Yuri Lyubimov has been able to connect into the performances of the Taganka Theatre all the elements of Russian Culture in a kind of global performance of them. The five representative performances, that we have submitted to analysis, are bound by the post – modern (and post – dramatic) use of literary, artistic, historical quotations in an intensive dialogue with the texts of Tradition and with the spectators of many generations.